Pengaruh Person Organization Fit terhadap Employee Outcomes dengan Job Satisfaction sebagai Variabel Intervening - Dominicus Wahyu Pradana; Daniel Tulasi (Universitas Medan Area, 2021)
This study examines the factors that influence employee outcomes, using the dimensions of person organization fit, namely the values congruence, personality congruence, work environment congruence, and job satisfaction as an intervening variable. This research belongs to the category of conclusive research that seeks a causal relationship between person organization fit and employee outcomes through job satisfaction. There are 7 hypotheses proposed to prove the direct or indirect effect between the independent and dependent variable through the intervening variable. Data was collected using a survey method with data collection tools in questionnaires distributed to administrative employees at private universities in Surabaya as many as 104 respondents. After the data is collected, then it is processed and analyzed using SEM-PLS 3.0. Based on the results of the analysis and discussion of the relationship between the factor of person-organization fit and employee outcomes (EO) which in this study is proxied by organizational commitment (organizational commitment), the integrative conclusion of this study is that person organization fit (PO fit) can affect employees outcome either directly or through job satisfaction as an intervening variable